Effect of carry-over on the kinetics of chlorine dioxide delignification of an unbleached hardwood kraft pulp - Simões, Rogério (2010)
This work is concerned with the kinetics of the prebleaching stage of a kraft pulp of Eucalyptus globulus with chlorine dioxide. Its main purpose is to discuss the influence of the degree of washing, expressed as the COD of the pulp, on the kinetics and stoichiometry of chlorine dioxide delignification. The effect of the carry-over on the rate of delignification of a Do stage was studied over time for pulps with different initial organic charges (COD). A set of experiments was specially designed to discriminate the individual role of lignin and of COD upon the initial consumption of chlorine dioxide. A modified mathematical model, taking into account the reactions of chlorine dioxide with both lignin and the carry-over, has been developed. In this model, the initial chlorine dioxide consumption (in the fast phase of reaction) is dependent on two factors: the carry-over of the pulp and the temperature of operation. However, the carry-over does not affect the corresponding initial depletion factor for the Kappa number. The role of the dissolved organic material, carried with the pulp, upon the rate of reaction in the slow period is better described in the stoichiometry. The fit of the experimental results obtained for pulps with different COD reveals good prediction capabilities for both Kappa number and chlorine dioxide concentration in a conventional D0 stage.